The Effectiveness of Expressive Writing Therapy in Improving Student Academic Resilience - Maindah Nur Laili Asari; Muzayyanatun Ni'mah; Novia Damayanti; Lufiana Harnany Utami (Faculty of Psychology, Universitas Semarang, 2023)
Pressure in undergoing the academic process in lectures often makes students feel stressed which can reduce student academic resilience. This study aims to see the effectiveness of expressive writing therapy on increasing academic resilience. Using quantitative experimental research method with a Two Group PreTest PostTest Design, this study involved 20 students who were divided into an experimental group and a control group. The measuring instrument used is the Resilient Questionnaire Scale, which is constructed based on seven resilience aspects by Reivich and Shatte. Data analysis using paired sample T-Test in the experimental group showed a pretest score of 130.93 and a posttest score of 213.40 with the Sig. value obtained. (2-tailed) of 0.000 < 0.05. These results indicate an increase in posttest scores in the experimental group, so the applied expressive writing therapy appears to be effective in enhancing academic resilience in studentsKeywords: Expressive Writing Therapy, Academic Resilience, Students